Prevalence of bacteria and fungi in respiratory tracts of seabirds rescued along the São Paulo Southeastern Coast (Brazil) and some blood parameter information - Del Busso Zampieri, Bruna [UNESP]; Siems, Thais Leandra [UNESP]; De Oliveira, Raphaela Sanches [UNESP]; Pinto, Aline Bartelochi [UNESP]; De Oliveira, Ana Julia Fernandes Cardoso [UNESP] (My University, 2015)
Seabirds can be affected by both bacterial and fungal diseases. Pollution in coastal regions is increasing as a result of domestic sewage and a lack of sanitation. Marine vertebrates can be infected by etiological agents, by water contamination, or by feeding on contaminated prey while foraging. Thus, this study aims to characterize the bacterial and fungal groups found in the respiratory tracts of seabirds from the southeastern coast of Brazil in attempt to identify infectious diseases that may be of risk to humans or other animals sharing the environment. Staphylococcus spp. and Streptococcus spp. were found to be the most prevalent of the bacteria isolated, while Candida spp. and Aspergillus spp. were the most frequently isolated fungi. The results suggest possible fungal and bacterial infections due to heterophilia associated with leukocytosis. Fungi appeared to have a higher impact on blood parameters than bacteria did, even though bacteria make up most of these animals' commensal organisms. Some microorganisms, such as Aspergillus spp., appear to develop into more severe diseases and to generate higher mortality rates in species that are less frequently found along the Brazilian coast, such as Spheniscus magellanicus.
Keywords: Aspergillus sp; Bacteria; Rehabilitation; Respiratory diseases; Seabirds; Zoonoses